The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3906/biy-1901-34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B2O3 (boron trioxide) on colon cancer cells: our first-step experience and in vitro results

Abstract: Boron oxide (B 2 O 3 ) is derived from dehydration of boric acid and is a colorless, semitransparent, crystalline compound that is moderately soluble in water. On the other hand, boron oxide is chemically hygroscopic. This gives the molecule the ability to soak up water and adhere to tissues. Boron oxide can be used locally after tumor debulking in inoperable tumors and especially when the tumor-free margin distance cannot be provided. For all these reasons we aimed to evaluate the in vitro test results of B 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although it is better that the target cells have the same origin, but since fibroblasts have many characteristics in the tumor microenvironment, in this study, L929 cells were used as a control, and according to ATCC1 ANIMAL CELL CULTURE LINE, these cells are mouse dermal fibroblasts. These cells were widely used as normal cells in many cancer studies for comparing metabolic activity of the target cells [55][56][57][58][59]. Fibroblasts are the principal stromal cells that exist in the whole body and are widely distributed throughout the organs…”
Section: Plos Onementioning
confidence: 99%
“…Although it is better that the target cells have the same origin, but since fibroblasts have many characteristics in the tumor microenvironment, in this study, L929 cells were used as a control, and according to ATCC1 ANIMAL CELL CULTURE LINE, these cells are mouse dermal fibroblasts. These cells were widely used as normal cells in many cancer studies for comparing metabolic activity of the target cells [55][56][57][58][59]. Fibroblasts are the principal stromal cells that exist in the whole body and are widely distributed throughout the organs…”
Section: Plos Onementioning
confidence: 99%
“…There is just one study focused on the effects of B 2 O 3 in colon cancer cells in the literature (Albuz et al, 2019). Therefore, our study (Strawn et al, 2006), and since then, a great number of studies have been conducted with different types of NPinduced toxicity (Baeg et al, 2018;Demir, 2020;Priyadarsini et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Induced ROS levels trigger inflammation response and DNA and protein damage (Cui et al, 2010;Ng et al, 2017) Several studies concerning boron compounds have revealed that some boron compounds showed genotoxic effects in GADD45a assay (Scott & Walmsley, 2015) and DNA strand breaks (Emanet et al, 2015). On the other hand, B 2 O 3 was investigated for the induction of micronuclei formation in ovary cells of Chinese hamsters; however, no such effect was found (Albuz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations